Analisis Program Pendayagunaan Zakat Produktif Z-Chicken Menggunakan Indeks Pendayagunaan Zakat (IPZ) (Studi Kasus Di BAZNAS Provinsi Banten) - Siti Febriyanti; Syihabudin Said; Isti Nuzulul Atiah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the effectiveness of the utilization of productive zakat through the Z-Chicken program organized by Baznas Banten Province. This type of research is qualitative with a descriptive approach with data collection through interviews, documentation, observation and distribution of questionnaires to mustahik. The results of the study indicate that the average IPZ value of the Z-Chicken program is 0.48 which is included in the less good category. Currently the Z-Chicken program is in the strengthening stage.